Home blood pressure telemonitoring for improving blood pressure control in middle‐aged and elderly patients with hypertension. Issue 9 (5th August 2021) - Yue, Jianwei; Yang, Xiaomin; Wang, Bin; Hu, Han; Fu, Haiming; Gao, Yuxia; Sun, Gang
Abstract: The blood pressure (BP) control rate among treated hypertensives in China remains low at 37.5%. The relationship between home blood pressure telemonitoring (HBPT) and BP control is controversial. The authors aimed to investigate the relationship between HBPT and BP control in middle‐aged and elderly hypertensives. In total, 252 hypertension patients aged between 60 and 79 years were enrolled. The patients were given either HBPT through interactive platforms between physicians and patients (telemonitoring group, n = 126) or conventional management (routine management group, n = 126). All patients were followed‐up for 15 months. BP control was defined as home systolic blood pressure < 135 mm Hg and home diastolic blood pressure < 85 mm Hg. At baseline, there were no significant differences in the baseline BP control rate ( p = .083). However, after 15 months, the BP control rate improved in both groups, and the telemonitoring group (71.3%) had a significantly higher BP control than the routine management group (49.8%) ( p < .001). The change of BP control rate from baseline in the routine management group increased by 26.1%, and that of the telemonitoring group increased by 35.4%. The results of the fully adjusted binary logistic regression showed that HBPT was positively associated with BP control after adjusting for confounders ( OR = 4.15, 95% CI 2.05–8.39). Similar results were observed after 3, 9, and 12 months. The association of HBPT with BP control was similar in subgroups. In conclusions, HBPT is recommended for BP control in middle‐aged and elderly hypertensives in the community setting.